Break point identification and spatiotemporal dynamic evolution of air pollutants: An empirical study from Anhui province, east China - Wang, Huajie; Gui, Herong; Wang, Houfeng; Liu, Guijian (Frontiers in Environmental Science, 2022)
The new mode of inter-regional joint prevention and control is increasingly important to the integrated process of collaborative governance of air pollutants. Thus, it is urgent affairs to analyze the interaction degree of air pollutants within and inter-cities, master spatiotemporal dynamic distribution and its influencing factors, and diagnose the primary obstacle factors. The long-term data onto air pollutants concentration were analyzed by using the harmonic regression, coupling coordination degree model, obstacle degree model, logarithmic mean divisian index (LMDI) and exploratory spatial data analysis (ESDA) among 16 cities of Anhui Province from 2015 to 2020. The overall trend of the annual mean concentration of air pollutants (NO2, SO2, CO, PM10 and PM2.5) in Anhui has decreased to a certain extent, whereas the trend of O3 was adverse. The biggest drop was 80.60 % of SO2 in BZ city (halving time: -2.03 ± 0.020 years), and O3 up 113.85% in CZ city (doubling time: 1.74 ± 0.01 years). The O3 concentration of most cities emerged to break points starting from 2018, but the break points of other air pollutants appear earlier than O3, nearly before 2018. Except for NO2 and O3, the halving time of other air pollutants was basically faster than the doubling time. The large interaction degree of air pollutants within and between cities has been contrasted sharply with the low coordination degree. The hotspots evolution of particulate matters (PM10 and PM2.5) was migrated to northern Anhui, NO2 and O3 were agglomerated to the central Anhui, and CO was eventually gathered in the Wanjiang City Belt. The primary obstacle factors of air pollutants in Anhui were particulate matter, SO2 and NO2. Seasonal differences in primary obstacle factors were highlighted in 2020: NO2 dominant in winter (10 cities) and the spring of southern Anhui was dominated by SO2 and particulate matter dominated remaining season. Industrial structure was more effective in reducing carbon emissions, and technological improvement was more advantageous in reducing industrial particulate matter, NOx and SO2. Ultimately, policy implications for strengthening inter-city air pollutants joint prevention and control were discussed.